Rancang Bangun Sistem Informasi Jalur Feeder untuk Mendukung Penanganan Fiber Cut pada Jaringan FTTH - Mutiara Putri, Adinda; Wulandari, Asri; Damar Hayyu Raharjo (Elektrika, 2025)
FTTH (Fiber to the Home) is a fiber optic-based telecommunication network technology that provides direct internet services to customers' homes. One of the challenges in its implementation is the occurrence of disruptions caused by fiber cuts, which affect service quality. This study designs a feeder route information system using an interactive map to facilitate the identification process of affected feeder lines and customers. The system is developed using the Laravel and React.js frameworks, and utilizes Leaflet as a mapping library based on OpenStreetMap. System development follows the waterfall method, consisting of the stages: requirement, design, implementation, verification, and maintenance. The testing results of the feeder route visualization system and blast message feature indicate that the system has been successfully implemented and meets all functional criteria. Website testing was conducted based on three aspects: functional suitability, usability, and performance efficiency. The functional suitability aspect showed a feasibility rate of 100%, usability testing using the SUS method yielded an average score of 81 categorized as excellent, and performance efficiency testing produced an average score of 94%, classified as grade A. Therefore, this system is well-accepted and considered efficient in supporting the handling of fiber optic network disruptions.   Keywords: Fiber Optic; Fiber to the Home; Information System; Laravel; Leaflet   ABSTRAK      FTTH (Fiber to the Home) merupakan teknologi jaringan telekomunikasi berbasis fiber optik yang menyediakan layanan internet langsung ke rumah pelanggan. Salah satu tantangan dalam implementasinya adalah gangguan akibat terputusnya kabel (fiber cut) yang berdampak pada kualitas layanan. Penelitian ini merancang sistem informasi jalur feeder melalui peta interaktif untuk mempermudah proses identifikasi jalur feeder dan pelanggan yang terdampak oleh gangguan. Sistem ini dikembangkan menggunakan framework Laravel dan React.js, serta menggunakan Leaflet sebagai library pemetaan berbasis OpenStreetMap. Pengembangan sistem menggunakan metode waterfall dengan tahapan requirement, design, implementation, verification, dan maintenance. Hasil pengujian pada sistem visualisasi jalur feeder dan sistem blast message menunjukkan bahwa sistem telah berhasil dijalankan dengan baik dan memenuhi seluruh kriteria fungsional. Pengujian website dilakukan melalui 3 aspek, yaitu aspek functional suitability, usability, dan performance efficiency. Hasil aspek functional suitability menunjukkan sistem memiliki tingkat kelayakan sebesar 100%, pengujian usability menggunakan metode SUS menghasilkan skor rata-rata 81 yang termasuk dalam kategori excellent, dan pengujian performance efficiency memiliki nilai rata-rata 94% yang termasuk dalam grade A. Dengan demikian, sistem ini dapat diterima dengan baik dan dinilai efisien untuk mendukung penanganan gangguan jaringan fiber optik.